New Directions in American Political Parties - Edited by Jeffrey M. Stonecash (New York Routledge Taylor and Francis Group, 2010)
Our portraits of voters, their relationship to parties, and the behavior of elected party members have changed significantly. This volume brings together assessments of these changes to provide a comprehensive overview of the trends in the field. It is suitable for scholars and students of American politics generally.
Inlude Tables, Graphs, Bibliography and Index
Keywords: Political parties -- Politics and government